Infectious Complications after Osteosynthesis of Long Bones of the Lower Limbs: Clinical and Nosological Aspects - Kolov, H.B. (TERRA ORTHOPAEDICA, 2024)
Summary. The number of complications in the treatment of bone fractures, including infectious ones, remains significant. Therefore, there is a need to carry out all measures aimed at improving the treatment results for this category of patients. Objective. The objective of our study was to determine the frequency and structure of infectious complications in patients after osteosynthesis of the long bones of the lower limbs depending on the location and type of osteosynthesis. Material and Methods. For our study, 140 cases of infectious complications after osteosynthesis of long bones of the lower limbs were analyzed. Results. An integral analysis of the distribution of the retrospective array of studies based on localization in the femur revealed that the infectious process is most often localized in patients with 32B hip fractures. This type of damage was observed in 29.0% of patients of the general array, where it took the first place. Infectious complications after plate osteosynthesis also prevailed, but were detected less often, in 21.2% of cases. Among the patients after blocking intramedullary osteosynthesis, 32B was detected in more than half of the cases, which is 2.5 times more often than among the patients with plate fixation. Similar results were found in patients with damage to the shin. Conclusions. The results of the analysis indicate that in cases of infectious complications after osteosynthesis of the bones of the lower extremities, damage to the diaphyseal part of the hip was detected most often. This indicates that the development of infectious complications was significantly influenced by the patient’s condition and the intervention performed.